ATP-sulfurylase, sulfur-compounds, and plant stress tolerance - Anjum, Naser A.; Gill, Ritu; Kaushik, Manjeri; Hasanuzzaman, Mirza; Pereira, Eduarda; Ahmad, Iqbal; Tuteja, Narendra; Gill, Sarvajeet S. (Frontiers in Plant Science, 2015)
Sulfur (S) stands fourth in the list of major plant nutrients after N, P and K. Sulfate (SO42-), a form of soil-S taken up by plant roots is metabolically inert. As the first committed step of S-assimilation, ATP-sulfurylase (ATP-S) catalyzes SO42--activation and yields activated high-energy compound adenosine-5′-phosphosulfate (APS) that is reduced to sulfide (S2-) and incorporated into cysteine (Cys). In turn, Cys acts as a precursor or donor of reduced S for a range of S-compounds such as methionine (Met), glutathione (GSH), homo-GSH (h-GSH) and phytochelatins (PCs). Among S-compounds, GSH, h-GSH and PCs are known for their involvement in plant tolerance to varied abiotic stresses, Cys is a major component of GSH, h-GSH and PCs; whereas, several key stress-metabolites such as ethylene, are controlled by Met through its first metabolite S-adenosylmethionine. With the major aim of briefly highlighting S-compound-mediated role of ATP-S in plant stress tolerance, this paper: (a) overviews ATP-S structure/chemistry and occurrence, (b) appraises recent literature available on ATP-S roles and regulations, and underlying mechanisms in plant abiotic and biotic stress tolerance, (c) summarizes ATP-S-intrinsic regulation by major S-compounds, and (d) highlights major open-questions in the present context. Future research in the current direction can be devised based on the outcomes of the discussion.